Implementasi Profetik Di Lembaga Pendidikan Dasar - Yayuk Zulaikah; Imam Fuadi; Ahmad Tanzeh; Kojin Kojin; Binti Maunah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The purpose of writing this article is to determine the implementation of prophetic in basic education institutions. This research uses a type of library research. Library research is research carried out by reviewing various journals and related reference books. The results of his research show that the prophetic leadership paradigm is a leadership paradigm that refers to the leadership concept of the prophets or Apostles of Allah SWT. Where this prophetic paradigm is a set of theories that not only describes and transforms social phenomena, and does not just change things for the sake of change, but more than that, it is hoped that it can direct change on the basis of ethical and prophetic ideals. From the description of the verses of the Koran, hadith, and theoretical views, which are relevant to the values ​​of the mission sent by the prophets, there are several indications or characteristics that could be seen as a prophetic leadership paradigm. Among these characteristics are: a) Smart, analytical and critical (fathanah); b) Tabligh, firm, brave and upholding justice and honesty; c) Gentleness and compassion; d) Bringing the mission of monotheism (transcendental). Then, other prophetic leadership values ​​or characteristics include: Smart, analytical and critical (fathanah); Tabligh, firm, brave and upholding justice and honesty; Gentleness and compassion; Bringing the mission of monotheism (transcendental); have a progressive vision; Have moral responsibility; Have managerial abilities; Sincere and have a spirit of dedication and devotion; Trustworthy and fair; Carrying the mission of worship and monotheism; Zuhud, honest and good at socializing or interacting with others; Become a role model for subordinates; Wise, forgiving and tolerant; Optimistic, patient and moral al-Karimah; has a reforming spirit and professionalism. Apart from that, the prophetic leadership paradigm is a necessity to be implemented and at the same time becomes the spirit in the implementation of leadership in Islamic educational institutions. Everything is a means to create the benefit of the people and solely.